Fabrication and characterization of porous Si and embedded porous Si for photonics application / Rihana Yusuf and Alhan Farhanah Abd Rahim - Yusuf, Rihana; Abd Rahim, Alhan Farhanah (Research Management Institute (RMI), 2012)
The development of nanoelectronics demands the implementation of new materials that should be Si-compatible but with enhanced electric and photonic properties for further device scaling. Si/Ge can be considered as a useful and promising material for this purpose. However in photonics, Si and Ge suffer from their poor optical properties and cannot compete with the direct bandgap semiconductors^, g GaAs). Si/SiGe nanostructures need to offer new solutions for improving the optical efficiency of the materials. Ge nanostructures have attracted world-wide attention due to their interesting quantum effects both in electronics and photonics application[l]. A variety of techniques have been employed to grow such structures, the most popular one is self-assembled growth nanometer islands in highly strained system using sophisticated Molecular Beam Epitaxy (MBE) or Low Pressure Chemical Vapor Deposition(LPCVD) techniques[2-5]. However these techniques require sophisticated machine and the cost is very high. In addition, the discovery of room temperature photoluminescence in porous silicon (PS)[6], presents a great interest in optoelectronic studies of this material. Covering or filling the pore network of a PS layer to produce a silicon nanocomposite is a promising process for new potential optoelectronics applications. Hence, there is a need to find a cost effective technique to grow a quality Ge nanostructures for photonics application. In this work, an effective and low cost method of thermal evaporation is used to fabricate the Ge nanostructure while low cost porous silicon will be utilized as the patterned substrate for the Ge nanostructure inclusion. Although there is still lack of commercially valuable Si-based active photonic devices, efficient light sources and detectors based on Si/SiGe would be a breakthrough that will open possibilities for the new systemon- a-chip to incorporate photonic devices with Si nanoelectronics. Si and Ge -based photodetectors are probably the most attractive candidate for this purpose due to possibility of integration into the logic IC chips.Hence, it is therefore of high interest to study the structural and optical characteristics of Ge nanostructure embedded inside porous silicon for effective light emission and detection.